Optimalisasi Pengelolaan Homestay sebagai Alternatif Akomodasi Wisata Studi Kasus: Destinasi Pulau Pahawang - Rifka Simbolon; Yunita Fitri Yanti; Yudha Sakti Pratama (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Homestay is one of the alternative forms of accommodation that has been rapidly developing in community-based tourism areas. As part of sustainable tourism development strategies, homestays are expected not only to provide lodging but also to serve as a medium for interaction between tourists and local communities. This study aims to evaluate the implementation of homestay business standards based on the Regulation of the Ministry of Tourism and Creative Economy Number 9 of 2014 in Pahawang Island Tourism Village, Punduh Pidada Subdistrict, Pesawaran Regency. This research uses a qualitative approach with descriptive-analytical methods. Data were collected through field observation, in-depth interviews, documentation, and questionnaires involving eleven homestay units located in Dusun 3 Jelarangan. The results indicate that while most homestays meet the basic accommodation needs of tourists, they have not fully complied with national business standards. Two homestays were categorized as "good," while the remaining nine were classified as "adequate." Product aspects such as the availability of bedrooms and kitchens are generally fulfilled; however, safety facilities and supporting infrastructure remain inadequate. Service and management aspects are the main weaknesses, marked by the absence of Standard Operating Procedures (SOPs), administrative documentation, and training for homestay managers. The main barriers to standard implementation include limited resources, lack of understanding of regulations, and insufficient institutional support. In conclusion, homestays in Pahawang island hold great potential to be developed as competitive tourist accommodations. However, continuous assistance, managerial training, and integrated institutional support are needed to achieve optimal service quality and strengthen destination competitiveness.